Characterization of 67 Confirmed Clustered Regularly Interspaced Short Palindromic Repeats Loci in 52 Strains of Staphylococci - Wang, Ying; Mao, Tingting; Li, Yinxia; Xiao, Wenwei; Liang, Xuan; Duan, Guangcai; Yang, Haiyan (Frontiers in Microbiology, 2021)
Staphylococcus aureus (S. aureus), which is one of the most important species of Staphylococci, pose a great threat to public health. Clustered regularly interspaced short palindromic repeats (CRISPR) and their CRISPR-associated proteins (Cas) is an adaptive immune platform to combat foreign mobile genetic elements (MGEs) such as plasmids and phages. The aim of this study was to describe the distribution and structure of CRISPR-Cas system in S. aureus, and to explore the relationship between CRISPR and horizontal gene transfer (HGT). Here, we analyzed 67 confirmed CRISPR loci and 15 companion Cas proteins in 52 strains of Staphylococci with bioinformatics methods. Comparing with the orphan CRISPR loci in Staphylococci, the strains harboring complete CRISPR-Cas systems contained multiple CRISPR loci, direct repeat sequences (DR) forming stable RNA secondary structures with lower minimum free energy (MFE) and variable spacers with detectable protospacers. In S. aureus, unlike the orphan CRISPRs away from Staphylococcal cassette chromosome mec (SCCmec), the complete CRISPR-Cas systems were in J1 region of SCCmec. In addition, we found a conserved motif 5'-TTCTCGT-3' that may protect their downstream sequences from DNA interference. In general, orphan CRISPR locus in S. aureus differed greatly from the structural characteristics of the CRISPR-Cas system. Collectively, our results provided new insight into the diversity and characterization of CRISPR-Cas system in S. aureus.